Determinations of Employee Engagement: Servant Leadership, Training, Self-Efficacy Effects on Employee Performance - Susanto, Primadi Candra; Sawitri, Ni Nyoman; Ali, Hapzi; Rony, Zahara Tussoleha (Bulletin of Counseling and Psychotherapy, 2024)
This research aims to examine the influence of Employee Engagement through Servant Leadership, Training, and Self-Efficacy on Employee Performance. This research uses quantitative methods and questionnaires distributed to employees at international cargo expedition companies. The analysis tool used was SmartPLS version 3 software. The research results revealed that servant leadership had a positive impact on employee engagement in international cargo expedition companies, while training also had a positive impact. However, self-efficacy does not have a significant effect on employee engagement or performance. Theoretical contributions suggest that employee engagement can mediate the relationship between servant leadership and employee performance, and vice versa. The findings of this research are useful for the human resource department. However, this research has the limitation of researchers only focusing on employee performance and involvement in freight forwarding companies. This study recommends further research in other organizations.